Pengaruh Profitabilitas terhadap Nilai Perusahaan: (Studi Empiris Pada Perusahaan Sektor Industri Barang Konsumsi Di Bursa Efek Indonesia Tahun 2017-2019) - Jamaluddin Ali; Ridwan Faroji (Jurnal Neraca Peradaban, 2021)
This study aims to determine the effect of profitability (ROA, ROE and NPM) on firm value (PBV). The population in this study is the consumer goods industrial sector companies listed on the Indonesia Stock Exchange. The retrieval method uses the Purposive Sampling method. Samples were collected from 21 consumer goods industrial sector companies listed on the Indonesia Stock Exchange during the 2017-2019 period. The research used is associative research with a quantitative approach. The data analysis technique used descriptive statistics, classical assumption test: normality, multicollinearity test, heteroscedasticity test, autocorrelation test. While testing the hypothesis using multiple linear regression analysis using the help of IBM software Statistical Product for the Service Solution (SPSS) 26.0 for windows. The results of this study show that partially profitability (ROA) has a negative and significant effect on the firm value (PBV) of consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period. Meanwhile, Profitability (ROE) and Profitability (NPM) have a positive and significant effect on the firm value (PBV) of companies in the consumer goods industry listed on the Indonesia Stock Exchange for the 2017-2019 period. Simultaneously, profitability (ROA, ROE and NPM) has a positive and significant effect on firm value.